A new epigenetic marker: the replication-coupled, cell cycle-dependent, dual modification of the histone H4 tail - Fidlerová, Helena; Kalinová, Jana; Blechová, Miroslava; Velek, Jiří; Raška, Ivan (Journal of structural biology, 2009)
Recently, we described the cold-dependent detection of an epitope, epiC, that was selectively recognized by a monoclonal anti-actin antibody at 4 degrees C, but not at RT, in the early replicating chromatin domains of human fibroblast cell nuclei and chromosomes. EpiC was present in a distinct cell cycle window extending from S-phase throughout mitosis until early G1-phase of the next cell generation, indicating its possible involvement in the transfer/maintenance of epigenetic information on transcriptionally competent parts of the genome. However, the molecular nature of epiC remained unresolved. Here we identified epiC as a dual post-translational modification on the same histone H4 tail, which was immunodetected for the first time. We show that the antibody selectively recognized a synthetic peptide of the histone H4 region K12-L22 containing acetylated K16 and dimethylated K20 (H4K16ac-K20me2) at 4 degrees C, but not at RT. Moreover, we show that the peptide containing acetylated K16 and either unmodified or monomethylated K20 was recognized by this antibody at both temperatures. The present and previous results together indicate that, by acetylation of histone H4 K16 during S-phase, the early replicating chromatin domains acquire the H4K16ac-K20me2 epigenetic label that persists on the chromatin throughout mitosis and become deacetylated during early G1-phase of the next cell cycle.
Keywords: histony; Temperature; Cell Line; posttranslační úpravy proteinů; vysokoúčinná kapalinová chromatografie; Epitopes; metylace; epigeneze genetická; Methylation; epitopy; Protein Processing, Post-Translational; elektroforéza v polyakrylamidovém gelu; Chromatography, High Pressure Liquid; Immunoblotting; Electrophoresis, Polyacrylamide Gel; lidé; Humans; Acetylation; Cell Cycle; Peptides; buněčné linie; acetylace; imunoblotting; peptidy; Histones; buněčný cyklus; teplota; Epigenesis, Genetic